Ocampo, Victoria y Jacques Maritain. No sé rezar. Cartas y otros textos 1936-1943. Buenos Aires, Editorial Sur, 2021, 237 págs. - Mayorga, Elisa (2022)
Fil: Mayorga, Elisa. Universidad del Salvador; Argentina